The impact of a training curriculum for the development of explosive force and the completion of its lifting (Bang Press) among weightlifters with special needs - Nafea Kamil, lhab; Khamees jaber, Khalid; Majeed Salall, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Sports training aims to raise the level of achievement, and the remarkable achievements in various sports came as a result of the use of modern methods and training methods based on scientific foundations that enabled athletes to reach the highest level in sports championships. The use of unusual training curricula for the purpose of creating a qualitative breakthrough in the development of achievement, as well as the development of the physical qualities of players. Because I have been training in the weightlifting hall at Diyala Sports Club for three years, I noticed a weakness in the completion of the sleeping pressure lift (Bing Press) among players with special needs in Diyala province due to a weakness in the maximum strength of the muscles due to the departure of coaches and lack of interest in using different exercises from the usual. For what the researcher sees through his modest and simple experience, the development of a different training curriculum is different from classical training. The researcher’s training curriculum exercises in the development of the explosive power of players with special needs contributed to the raising of the Bing Press in addition to achieving the training mechanism for the different curriculum for classical exercises in the development of maximum strength in players.